Peran Kepuasan Pengunjung Sebagai Mediator Atribut Pariwisata dan Kualitas Layanan Terhadap Niat Berkunjung Kembali: (Studi Kasus: Pantai Pulo Silalahi - Sumatera Utara) - Silalahi, Agnes Tresia; Hutama, Surya Tri Esthi Wira (TOBA: Journal of Tourism, Hospitality, and Destination, 2023)
Pulo Silalahi Beach is a tourist attraction in the newly developing Lake Toba Super Priority Tourism Area, so it is necessary to evaluate the elements of the tourist attraction on visitor behavior patterns. This research aims to determine the relationship between tourism attributes and service quality on visitor satisfaction and intention to return to Pulo Silalahi Beach, North Sumatera. The method used is descriptive analysis using SPSS and SmartPLS with 100 respondents determined by purposive sampling. The results of the research show that the tourism attribute variable has a positive and significant direct influence on intention to revisit, and visitor satisfaction, and has a positive and significant indirect influence on intention to revisit through visitor satisfaction. The service quality variable does not have a direct effect on the intention to visit again, it has a positive and significant direct effect on visitor satisfaction and an indirect positive and significant effect on the intention to visit again through visitor satisfaction. The Visitor Satisfaction variable positively and significantly affects the intention to visit again. The seven relationships tested show that visitor satisfaction and intention to revisit can be formed through adequate tourism attributes and good service quality, and visitor satisfaction acts as a mediator for tourism attributes, service quality, and intention to revisit. This research concludes that visitor satisfaction is the main indicator that managers must achieve through tourism attributes and service quality to increase tourists' intention to return to Pulo Silalahi Beach.